Prioritized Commitment-Based Clinical Assessment: A New Method for Assessment of Orthodontic Treatment Outcomes - Seyed Mohammadreza Safavi; Arash Farzan; Farnaz Younessian; Alireza Akbarzadeh Baghban (Galenos Yayinevi, 2021)
Objective: Quality assessment is an essential part of orthodontic treatment. Most of the current indices are essentially based on occlusal assessment. However, an ideal occlusion is only one aspect of an ideal treatment. The aim of this article is to introduce a new prioritized commitment-based clinical assessment (PCCA) method and present its reliability and linear correlation test in comparison with the comprehensive clinical outcome assessment (CCA).Methods: One hundred treated cases were scored with the conventional assessment tool--the CCA--and the newly developed assessment tool--the PCCA--with 2 calibrated examiners at 2 different time intervals. These cases were randomly selected including equal numbers of the main malocclusions managed with fixed conventional edgewise appliances within the past 3 years and had complete pre-treatment and post-treatment routine records. The intraclass correlation coefficient (ICC) was used to assess the intra- examiner repeatability of the total scores of both methods. Pearson's correlation coefficients were computed to assess the linear relationships between the CCA and PCCA scores.Results: The intra-examiner reliability assessed for CCA and PCCA showed high repeatability for both examiners (ICC: 0.93 and 0.945, respectively). The inter-examiner reliability values for CCA and PCCA, assessed by ICC, were 0.84 and 0.96, respectively. The linear correlation between the 2 methods, assessed by comparing the mean score of each case by the 2 examiners was significant, at 0.01.Conclusion: The PCCA method can be used for quality assessment in treated orthodontic patients. The preliminary test of the new method presented good inter- and intra-observer agreements and a significant linear correlation with the CCA method.